(untitled) (Journal of Computational Mathematics, 2001)
In this paper, some estimations of bounds for determinant of Hadamard product of H-matrices are given. The main result is the following if A = (a_ij) and B=(b_ij) are nonsingular H-matrices of order n and ∏^n_i=1a_iib_ii ＞ 0, and A_k and B_k, k=1, 2, …, n, are the k × k leading principal submatrices of A and B, respectively, then where M(A_k) denotes the comparison matrix of A_k.